The Relationship Between Teacher Self-Efficacy and the Ability to Integrate Technology Literacy in Civics Learning in Banda Aceh - Susatyo Adhi Pramono; Rusli Yusuf; Nanda Saputra; Heni Novita Sari; Mia Aina; Anta Rini Utami (STAI Hubbulwathan Duri, 2023)
An essential element that must be considered, especially by the teacher, is the integration between technology and the teaching-learning process. The study's problem formulation, as well as its purpose is to investigate whether there is a relationship between teacher self-efficacy and technology integration in Civics learning. The hypothesis of this study is that there is a substantial association between teacher self-efficacy and the ability to integrate technology into the civics learning process. This is demonstrated by the technique, results, and implications. This study used quantitative research and correlational analysis to examine the relationship between teacher self-efficacy and the ability to integrate technology into the Civics curriculum. The instrument used consisted of a self-efficacy questionnaire and technology integration. The study's results showed a positive relationship indicated by the correlation coefficient value of 0.839 0.254 with the Sig. (2-tailed) of 0.000 0.05 that showed a relationship between teacher self-efficacy and the ability to incorporate technology into civics education. It is better if the learning process continues to be carried out by integrating technology into learning. So that children can have the ability to use technology following current developments. Besides that, teachers or educators must continuously learn and participate in training to improve the ability to use technology in the learning process.